Radio Frequency Identification Based System Design For Logistics Application - Jamaludin, Zamberi; Huong, Yu Chung; Abdullah, Lokman (Penerbit Universiti, UTeM, 2017)
Recently,RFID has been the focal point of technology in automatic information transfer mechanism to enhance product visibility throughout supply chain.In logistics and manufacturing,it is of utmost important to optimize utilization and control of material flow.This paper outlines the design approach for application of RFID technology in supply chain with focus on logistics process such as distribution,storage and delivery.The automatic device tracking system via RFID technology outlined in this paper is to be implemented in an actual manufacturing plant.The primary objective is to extend the benefits of RFID deployment in actual industrial application for cost reduction and improved efficiency. Conclusions and potential future advances are presented at the end of this paper.